Odpowiedzi

2009-11-17T16:44:13+01:00
A) x+(3x-y2+7)= x + 3x - 2y - 7 = 4x - 2y - 7
b)-a+(2a-3b-1)= -a + 2a - 3b - 1 = a - 3b - 1
c)-x2+(x2 -x-7)= -2x + 2x - x - 7 = -x - 7
c)-b3-(b3-b2-b)= -3b - 3b + 2b + b = -3b
Najlepsza Odpowiedź!
2009-11-17T16:44:40+01:00
A) x+(3x-y2+7)=x+3x-y²+7=4x-y²+7
b)-a+(2a-3b-1)=-a+2a-3b-1=a-3b-1
c)-x2+(x2 -x-7)=-x²+x²-x-7=-x-7
c)-b3-(b3-b2-b)=-b³-b³+b²+b=-2b³+b²+b
2009-11-17T16:45:14+01:00
A) x+(3x-y2+7)= x +3x -y2 +7= 4x -y2 +7
b)-a+(2a-3b-1)= -a +2a -3b - 1=-a - 3b -1
c)-x2+(x2 -x-7)= -x2 +x2 -x -7= -x - 7
c)-b3-(b3-b2-b)= -b3 -b3 +b2 +b= b2 +2